Kajian Sistem Jaringan Drainase Guna Menanggulangi Genangan Air Hujan Di Kawasan Pasar Pajak Pagi Kutacane: Study of the Drainage Network System to Overcome Rainwater Puddles in the Kutacane Morning Tax Market Area - K Anwar (Jurnal MESIL (Mesin Elektro Sipil), 2022)
Puddles or floods that occur in an area are caused by a disturbed or malfunctioning drainage system. The research location was conducted in the Kutacane Morning Tax market area. The calculation of the rainfall intensity used for this study is by using the mononobe formula with the parameters for calculating the rainfall value of the Pearson III Log Distribution for a 5-year return period. The Kirpich equation determines the concentration time. From the results of the research, it turns out that the Tax channel in the Morning Tax market is not able to drain puddles of rainwater, which causes puddles in the market area, and the Disposal channel, which is a drainage channel in the market, does not function because it is clogged with sedimentation so that the Tax channel is unable to accommodate and drain high-intensity rainwater discharge. In order to avoid inundation in the morning tax area, the dimensions of the channel are redesigned, where the existing dimensions are the tax channel with dimensions h = 0.65 m, B = 0.85 m, f = 0.15 m, with Q plans (m/ sec) = 1.219 and Q capacity (m/sec) = 0.498 with a description (Does not meet) Meanwhile, the dimensions of the redesigned tax channel are h = 0.781 m, , B = 0.781 m, f = 0.5 m, with Q plans ( m/s) = 1.219 and Q capacity (m/s) = 1.219 with the information (Qualified) the total length of the tax channel is 3,612 Km. For the existing sewer h = 0.65 m, , B = 0.85 m, f = 0.15 m, with a design Q (m/s) = 1.110 and a capacity Q (m/s) = 0.498 with a description (No meet) Meanwhile, the dimensions of the redesigned drain are h = 0.832 m, , B = 832 m, f = 0.5 m, with Q plan (m/sec) = 1,110 and Q capacity (m/sec) = 1,110 with information (Qualified) total length of Exhaust channel 0.421 Km.